(untitled) (Nóema, 2015)
This article is about Whitehead’s metaphysics. We focus on operations constituting the processual character of this philosophy. The approached problems are the organization of genetic space of concrescence and co-ordinate space of transition, the complex dynamics between nature and abstraction then the reciprocity between a subjective and affective formation and a neutral temporality of duration’s blocks. The intuition behind our reflection is that there is a principal concept which animates Whitehead’s cosmology of Creativity : the concept of Becoming.